2022
DOI: 10.1002/ajh.26451
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcomes among newly diagnosed patients with FMS‐like tyrosine kinase 3 internal tandem duplication mutated acute myeloid leukemia treated with contemporary therapy: Revisiting the European LeukemiaNet adverse risk classification

Abstract: Mutations in fms-like tyrosine kinase 3 (FLT3) gene are common genomic alterations in acute myeloid leukemia (AML). FLT3 internal tandem duplication mutations (FLT3-ITD) have consistently been shown to be adversely prognostic, particularly those with high allelic ratio (AR). Current AML treatment strategies, including high dose cytarabine, purine analogs, FLT3 inhibitors (FLT3i), and with or without allogeneic stem cell transplant (SCT) have been shown to improve the outcomes in patients with FLT3 mutations. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…9,10 The diminishing prognostic role of FLT3-ITD mutations under contemporary therapy in AML has been underlined in a recent report and underscores the need to account for not only response to but also type of induction chemotherapy, in assessing prognostic relevance. 11 Regardless, the observations from the current study highlight the value of considering post-treatment variables as formal components of survival prediction in AML, a concept that is also being pursued in acute lymphoblastic leukemia 12,13 and chronic myeloid leukemia. [14][15][16] In this regard, it should be noted that CR/CRi is a morphologic definition whose value as a prognostic marker might be further enhanced by targeting molecular or cytogenetic remission, as well as assessment of minimal residual disease (MRD); unfortunately, MRD data were not readily available in the current retrospective study.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…9,10 The diminishing prognostic role of FLT3-ITD mutations under contemporary therapy in AML has been underlined in a recent report and underscores the need to account for not only response to but also type of induction chemotherapy, in assessing prognostic relevance. 11 Regardless, the observations from the current study highlight the value of considering post-treatment variables as formal components of survival prediction in AML, a concept that is also being pursued in acute lymphoblastic leukemia 12,13 and chronic myeloid leukemia. [14][15][16] In this regard, it should be noted that CR/CRi is a morphologic definition whose value as a prognostic marker might be further enhanced by targeting molecular or cytogenetic remission, as well as assessment of minimal residual disease (MRD); unfortunately, MRD data were not readily available in the current retrospective study.…”
Section: Discussionmentioning
confidence: 80%
“…The inclusion of response to treatment as a risk variable, in the Mayo 3‐factor model, might have also modified the pattern of survival impact from mutations 9,10 . The diminishing prognostic role of FLT3 ‐ITD mutations under contemporary therapy in AML has been underlined in a recent report and underscores the need to account for not only response to but also type of induction chemotherapy, in assessing prognostic relevance 11 . Regardless, the observations from the current study highlight the value of considering post‐treatment variables as formal components of survival prediction in AML, a concept that is also being pursued in acute lymphoblastic leukemia 12,13 and chronic myeloid leukemia 14–16 .…”
Section: Discussionmentioning
confidence: 99%
“…AML is predominantly occurring in older adults and is mostly unsuitable for intensive therapy, due to a variety of poor prognostic factors, including a high proportion of poor cytogenetics, changes associated with myelodysplastic abnormalities, a high ECOG-PS score, and a combination of severe underlying disease [ 16 ]. The active ingredient of azacytidine and B-cell lymphoma/leukemia-2 inhibitors binds to RNA and DNA by interfering with RNA transcription and DNA of actively proliferating cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a Canadian CCO study on the efficacy of azacytidine on AML/MDS, the ORR was 28.0%, and the median survival time was 11.6 months [ 19 ]. AZA-001 studies showed that azacytidine and B-cell lymphoma/leukemia-2 inhibitors had an ORR of 29.0% and a median survival of 24.5 for treatment of high-risk MDS months; AZA-AML-001 study [ 16 ] shows ORR in the treatment of AML patients with azacytidine and B-cell lymphoma/leukemia-2 inhibitors. At 27.8%, the median survival time was 10.8 months, which was an improvement in response rate compared with traditional supportive care, and azacytidine significantly improved patients' objective response rate, survival rate, and clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, none of the immunotherapies used to treat hematological malignancies can completely replace allogeneic stem cell transplantation, but on the basis of their specific and clear mechanisms of action, they can be developed into more effective therapies with fewer side effects. Currently, patients undergoing immunotherapy treatment are sometimes at risk of serious side effects and, realistically, there are many hematologic malignancies with poor prognoses [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] even with novel therapies. In light of these challenges, it is important to consider what efforts can establish more curative immunotherapies for hematological malignancies.…”
Section: Introductionmentioning
confidence: 99%